Handbook of fermented meat and poultry (Blackwell Pub., 2008)
An internationally respected editorial team and array of chapter contributors has developed the Handbook of Fermented Meat and Poultry, an updated and comprehensive hands-on reference book on the science and technology of processing fermented meat and poultry products. Beginning with the principles of processing fermented meat and ending with discussions of product quality, safety, and consumer acceptance, the book takes three approaches: background and principles; product categories; and product quality and safety